2019
DOI: 10.5539/ijbm.v14n9p173
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating effect of Organizational Citizenship Behavior on the Organizational Justice and Organizational Performance in Small and Medium-Sized Enterprise of China

Abstract: This study examined the factors that influencing small and medium-sized enterprise (SMEs)’ performances with the mediating effect of organizational citizenship behavior in China. Its purpose is to motivate and improve the small and medium-sized enterprise’ performance. The examined factors were distributive justice, procedural justice, interactional justice. This study uses cross-sectional survey to verify the theoretical framework. The survey data in this study were collected from 251 empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Result of this also study are similar with past studies conducted by Selamat and Ran (2019) in which the found that employees who do not experience organizational fairness will be less productive and may even engage in undesirable idleness. As a result, organizational justice is a crucial factor in evaluating enterprise management competency and an essential element of a company's key competitiveness.…”
Section: Hypotheses Testing Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Result of this also study are similar with past studies conducted by Selamat and Ran (2019) in which the found that employees who do not experience organizational fairness will be less productive and may even engage in undesirable idleness. As a result, organizational justice is a crucial factor in evaluating enterprise management competency and an essential element of a company's key competitiveness.…”
Section: Hypotheses Testing Resultssupporting
confidence: 89%
“…Moreover, some other previous study also investigates the relationship between organizational justice and CWB. Selamat and Ran (2019) noted that the employee's reaction to such a violation is determined by organizational justice. If an employee is treated fairly, he will exhibit favorable attitudes and excellent morale in organization.…”
Section: Organizational Justice and Counterproductive Work Behaviormentioning
confidence: 99%
“…Similarly, Khokhar and Zia-ur-Rehman (2017) examined the positive and significant mediating role of OCB between TL, creativity, and ER. Selamat and Ran (2019) found that OCB significantly mediates the relationship between organizational justice and performance within SMEs in China. Chiang and Hsieh (2012) found that OCB partially mediated the relationship between perceived organizational support and job performance.…”
Section: Mediation Effect Of Organizational Citizenship Behaviormentioning
confidence: 92%
“…Organizational citizenship behaviour is a quality of employees that can distinguish one organization's performance from others (N. P. Podsakoff et al, 2009). Based on the research results, it has known that there is a significant relationship directly between meaningful work and organizational citizenship behaviour, with a percentage of 74 % (Selamat & Ran, 2019).…”
Section: Meaningful Work To Organizational Citizenship Behaviourmentioning
confidence: 99%